Receptor Interaction Profiles of 4-Alkoxy-Substituted 2,5-Dimethoxyphenethylamines and Related Amphetamines - Karolina E. Kolaczynska; Dino Luethi; Dino Luethi; Daniel Trachsel; Marius C. Hoener; Matthias E. Liechti (Frontiers Media S.A., 2019)
Background: 2,4,5-Trimethoxyamphetamine (TMA-2) is a potent psychedelic compound. Structurally related 4-alkyloxy-substituted 2,5-dimethoxyamphetamines and phenethylamine congeners (2C-O derivatives) have been described but their pharmacology is mostly undefined. Therefore, we examined receptor binding and activation profiles of these derivatives at monoamine receptors and transporters.Methods: Receptor binding affinities were determined at the serotonergic 5-HT1A, 5-HT2A, and 5-HT2C receptors, trace amine-associated receptor 1 (TAAR1), adrenergic α1 and α2 receptors, dopaminergic D2 receptor, and at monoamine transporters, using target-transfected cells. Additionally, activation of 5-HT2A and 5-HT2B receptors and TAAR1 was determined. Furthermore, we assessed monoamine transporter inhibition.Results: Both the phenethylamine and amphetamine derivatives (Ki = 8-1700 nM and 61-4400 nM, respectively) bound with moderate to high affinities to the 5-HT2A receptor with preference over the 5-HT1A and 5-HT2C receptors (5-HT2A/5-HT1A = 1.4-333 and 5-HT2A/5-HT2C = 2.1-14, respectively). Extending the 4-alkoxy-group generally increased binding affinities at 5-HT2A and 5-HT2C receptors but showed mixed effects in terms of activation potency and efficacy at these receptors. Introduction of a terminal fluorine atom into the 4-ethoxy substituent by trend decreased, and with progressive fluorination increased affinities at the 5-HT2A and 5-HT2C receptors. Little or no effect was observed at the 5-HT1A receptor for any of the substances tested (Ki ≥ 2700 nM). Phenethylamines bound more strongly to the TAAR1 (Ki = 21-3300 nM) compared with their amphetamine analogs (Ki = 630-3100 nM).Conclusion: As seen with earlier series investigated, the 4-alkyloxy-substituted 2,5-dimethoxyamphetamines and phenethylamines share some trends with the many other phenethylamine pharmacophore containing compounds, such as when increasing the size of the 4-substituent and increasing the lipophilicity, the affinities at the 5-HT2A/C subtype also increase, and only weak 5-HT2A/C subtype selectivities were achieved. At least from the binding data available (i.e., high affinity binding at the 5-HT2A receptor) one may predict mainly psychedelic-like effects in humans, at least for some of the compound investigated herein.